INHIBITION OF ESCHERICHIA COLI BY p-AMINOBENZOIC ACID AND ITS REVERSAL BY p-HYDROXYBENZOIC ACID - Davis, Bernard D. (The Rockefeller University Press, 1951)
p-Aminobenzoic acid (PABA) exerts three metabolic effects on E. coli: it acts as a normal vitamin at low concentrations, as a source of another vitamin, p-hydroxybenzoic acid (POB), at moderate concentrations, and as a growth inhibitor at high concentrations (150 to 1600 µg./ml.). The inhibition is competitively reversed by POB in 1/100 the concentration of PABA. The inhibition is also reversed to a limited extent by shikimic acid and compound X, precursors of POB. p-Nitrobenzoic acid is an inhibitory competitor of both POB and PABA. The retardation of growth produced by PABA and other competitive analogues of POB (p-nitrobenzoic acid; 4,4'-dihydroxydiphenyl sulfone; phenosulfazole) is converted to complete bacteriostasis by the addition of L-aspartic acid in a remarkably low concentration (1 µg./ml.)) without change in the competitive ratio with POB. The mechanism underlying this synergism is not clear. In contrast to wild type, mutants that require POB not only are inhibited by much lower concentrations of the above analogues, but also show inhibition by weaker competitors of POB such as p-hydroxybenzenesulfonamide, p-chlorobenzoic acid, and p-fluorobenzoic acid.